2012
DOI: 10.1073/pnas.1206036109
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-based high-content chemical library screening identifies statins as inhibitors of in vivo lymphangiogenesis

Abstract: Lymphangiogenesis plays an important role in promoting cancer metastasis to sentinel lymph nodes and beyond and also promotes organ transplant rejection. We used human lymphatic endothelial cells to establish a reliable three-dimensional lymphangiogenic sprouting assay with automated image acquisition and analysis for inhibitor screening. This high-content phenotype-based assay quantifies sprouts by automated fluorescence microscopy and newly developed analysis software. We identified signaling pathways involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 48 publications
2
57
0
Order By: Relevance
“…It has been shown that adenosine and other purines promote endothelial proliferation and migration in vitro [24,25], although results in more physiological models of sprouting angiogenesis have been contradictory [7,[26][27][28]. Therefore, we analyzed the role of extracellular purine metabolism on angio-and lymphangiogenesis using a quantitative model of sprouting [29]. Cultured human LECs used in the sprouting assays expressed higher levels of CD73 on their surface than the BECs and showed clear induction of sprouting after vascular endothelial growth factor A (VEGF-A) and bFGF stimulation ( Fig.…”
Section: Purinergic Signaling Contributes To Angiogenesis But Not To mentioning
confidence: 99%
“…It has been shown that adenosine and other purines promote endothelial proliferation and migration in vitro [24,25], although results in more physiological models of sprouting angiogenesis have been contradictory [7,[26][27][28]. Therefore, we analyzed the role of extracellular purine metabolism on angio-and lymphangiogenesis using a quantitative model of sprouting [29]. Cultured human LECs used in the sprouting assays expressed higher levels of CD73 on their surface than the BECs and showed clear induction of sprouting after vascular endothelial growth factor A (VEGF-A) and bFGF stimulation ( Fig.…”
Section: Purinergic Signaling Contributes To Angiogenesis But Not To mentioning
confidence: 99%
“…particularly during the early phases of the preclinical drug discovery process [31,32]. To underscore the importance of this approach, the first FDA approved antitubercular drug in over 40 years, bedaquiline [33], and others in advanced clinical development (Delamanid, Sutezolid and SQ109) were discovered through phenotypic screening [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell screening is getting renewed attention in the drug discovery process compared to target-based method [31,32]. Adopting whole-cell phenotypic screening approach, even for rationally designed ligands, has the unique advantage that it is able to interrogate all biochemical targets simultaneously in a specific physiological environment; Table 1: Synthetic yield for boronic-aurone derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…S1). The identification of statins as antilymphatic was expected as both compounds were recently shown to have antilymphatic properties (33). The secondary screen using fli1:egfp embryos identified kaempferol, leflunomide, cinnarizine, and flunarizine as agents that prevented lymphangiogenesis in the zebrafish without disrupting blood vessel development, whereas lovastatin and simvastatin disrupted ISV development at the screening dose of 5 mg/ mL.…”
Section: A Chemical Screen In Zebrafish Identified Drugs With Antilymmentioning
confidence: 99%